Improving Math Learning Result Using Stad Cooperative Model - Amnajuita Amnajuita (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. Problems to be studied in this research are: Does using STAD cooperative model can improve the learning result of mathematics? Steps taken in using the STAD cooperative model. The place of study is the place used in conducting research to obtain the desired data. This research took place at SD Negeri 08 Koto Berapak, Bayang District. The time of study is the time of the research or when the research is held. This study was conducted in the academic year 2017. The subjects of the study were the students of the second grade of SD Negeri 08 Koto Berapak, Bayang District, in the year of 2017 on the subject of mathematics. This research uses Classroom Action Research (PTK). According to the PGSM Project Trainers Team, the TOD is a reflective form of study by actors undertaken to enhance the rational stability of their actions in performing their duties, deepening their understanding of the actions, and improving the conditions under which the learning practices are conducted (in Mukhlis, 2000: 3). Meanwhile, according to Mukhlis (2000: 5) PTK is a form of review that is systematic reflective by the actors to improve the learning conditions undertaken. The main purpose of PTK is to improve / improve the learning pratek on an ongoing basis, while the purpose of inclusion is to grow a culture of research among teachers That is a set of plans and arrangements about classroom learning activities, as well as assessment of learning outcomes. It is a learning tool used as teacher's guidance in teaching and composed for each round. Each RP contains basic competencies, indicators of achievement of learning outcomes, specific learning objectives, and teaching and learning activities. The results of data analysis and discussion can show some of the progress achieved during learning either through classical learning, cooperative STAD model, playing quiz, or learning outcomes. So the results of this class action research can be drawn conclusions as follows: 1. Learning STAD cooperative model can encourage students to learn about math more excited, improve learning process, and learning outcomes. 2. Playing quiz can encourage students to learn about math to be more passionate, improve learning process, and learning outcomes. Some other findings obtained are the emergence of student creativity in making questions and answers, the number of questions posed by students, the responsibility of completing the task, the loss of boredom, even students prefer to complete the task rather than rest.